The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1364/oe.15.009877
|View full text |Cite
|
Sign up to set email alerts
|

Arrays of microlenses with variable focal lengths fabricated by restructuring polymer surfaces with an ink-jet device

Abstract: Abstract:We report of a method for fabricating two-dimensional, regular arrays of polymer microlenses with focal lengths variable between 0.2 and 4.5 mm. We first make concave microlenses by ink-jetting solvent on a polymer substrate with a commercial drop-on-demand device. Solvent evaporation restructures the surface by a series of combined effects, which are discussed. In the second step we obtain convex elastomeric microlenses by casting the template made in the first step. We demonstrate the good optical q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
(27 reference statements)
1
13
0
5
Order By: Relevance
“…Inkjet etching using drops of solvents on PS substrates has also been proposed to obtain polymer microstructures which can be used as microlenses [79,80,81]. Depending on the ratio of solvents in the jetted mixture the profile of the surface can be finely tuned going from concave to convex profiles in the same target substrate [80].…”
Section: Inkjet Printing For Micro-optics and Integrated Optics Famentioning
confidence: 99%
See 1 more Smart Citation
“…Inkjet etching using drops of solvents on PS substrates has also been proposed to obtain polymer microstructures which can be used as microlenses [79,80,81]. Depending on the ratio of solvents in the jetted mixture the profile of the surface can be finely tuned going from concave to convex profiles in the same target substrate [80].…”
Section: Inkjet Printing For Micro-optics and Integrated Optics Famentioning
confidence: 99%
“…Depending on the ratio of solvents in the jetted mixture the profile of the surface can be finely tuned going from concave to convex profiles in the same target substrate [80]. Later on, the inverse replica of these microlenses can be obtained by template casting using an elastomeric silicone (Sylgard 184, Dow Corning, Midland, MI, USA) [81]. …”
Section: Inkjet Printing For Micro-optics and Integrated Optics Famentioning
confidence: 99%
“…Nonetheless, this phenomenon can be used for deliberately modulating printed structures for many applications. For example it has been demonstrated that it can be used to fabricate concave and convex microlenses [7,8] and light emitting diodes (LEDs) [9] that can be used in optoelectronics. Studies on using inkjet or other dispensing tools to define structures in polymers and the influence of factors on the appearance and dimensions of the generated features have also been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…These polymer patterning investigations can be potentially useful in some structural or functional applications. Bonaccurso et al [17] and Pericet-Camara et al [18] used inkjet printing to fabricate microvessels and microlenses while Xia et al [19,20] and Lu et al [21] demonstrated using the same technique to create cavities for display applications.…”
Section: Introductionmentioning
confidence: 99%